Głos Łodzi . pismo Regionalnej Komisji Wykonawczej NSZZ "Solidarność", no. 28, 1985 - Popiełuszko, Jerzy; Katarasiński, Jerzy; Lerski, Witold ([s.n.], 1985)
Creation and circulation: W 1989 r. published legally titled Głos Solidarności